Treasures of America's national parks. 6, The Rockies & beyond [videorecording (DVD)]. (Distributed by Questar, 2008)
In Glacier National Park, reach up to the clouds among America's most scenic mountain pass, raft a wild river and take and unforgettable trek along the Highline Trail. Explore a region renowned for its panoramic beauty, icefields, and more.